1999
DOI: 10.1016/s0014-5793(98)01669-x
|View full text |Cite
|
Sign up to set email alerts
|

C‐terminal domains of human translation termination factors eRF1 and eRF3 mediate their in vivo interaction

Abstract: At the termination step of protein synthesis, hydrolysis of the peptidyl-tRNA is jointly catalysed at the ribosome by the termination codon and the polypeptide release factor (eRF1 in eukaryotes). eRF1 forms in vivo and in vitro a stable complex with release factor eRF3, an eRF1-dependent and ribosomedependent GTPase. The role of the eRF1ceRF3 complex in translation remains unclear. We have undertaken a systematic analysis of the interactions between the human eRF1 and eRF3 employing a yeast two-hybrid assay. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
117
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(125 citation statements)
references
References 31 publications
8
117
0
Order By: Relevance
“…Truncated eRF1 proteins and their binding to the C-terminal domain of S. pombe eRF3+ The activity of the eRF3C segment (amino acid positions 482-662) for binding to different truncated eRF1 polypeptides was examined by an in vivo two-hybrid system as well as by an in vitro pull-down analysis, as shown in Figure 4, and the data are summarized+ ϩ: binding, 6: weak binding; Ϫ: no binding+ The number refers to the amino acid position from the translation start site+ Sequence motifs homologous to domains III (acceptor stem mimicry), IV (anticodon helix mimicry), and V (T stem mimicry) of elongation factor EF-G are assigned (Ito et al+, 1996(Ito et al+, , 1998a)+ interaction of the C-terminal one-third domain of eRF3 per se with eRF1+ The present study has also confirmed the importance of the C-terminal acidic amino acid stretch of S. pombe eRF1 for binding to eRF3 (Ito et al+, 1998a)+ Following near completion of the revised manuscript after submission, we became aware of a recent study that warrants mention+ Merkulova et al+ (1999) have reported the similar C-terminal domain activity of human eRF3 for binding to eRF1+…”
Section: The C-terminal Domain Of Erf3 For Binding To Erf1supporting
confidence: 58%
“…Truncated eRF1 proteins and their binding to the C-terminal domain of S. pombe eRF3+ The activity of the eRF3C segment (amino acid positions 482-662) for binding to different truncated eRF1 polypeptides was examined by an in vivo two-hybrid system as well as by an in vitro pull-down analysis, as shown in Figure 4, and the data are summarized+ ϩ: binding, 6: weak binding; Ϫ: no binding+ The number refers to the amino acid position from the translation start site+ Sequence motifs homologous to domains III (acceptor stem mimicry), IV (anticodon helix mimicry), and V (T stem mimicry) of elongation factor EF-G are assigned (Ito et al+, 1996(Ito et al+, , 1998a)+ interaction of the C-terminal one-third domain of eRF3 per se with eRF1+ The present study has also confirmed the importance of the C-terminal acidic amino acid stretch of S. pombe eRF1 for binding to eRF3 (Ito et al+, 1998a)+ Following near completion of the revised manuscript after submission, we became aware of a recent study that warrants mention+ Merkulova et al+ (1999) have reported the similar C-terminal domain activity of human eRF3 for binding to eRF1+…”
Section: The C-terminal Domain Of Erf3 For Binding To Erf1supporting
confidence: 58%
“…The C-terminal region of eRF3 has been found to be the primary binding site for eRF1 (Ebihara and Nakamura 1999;Merkulova et al 1999). In this region, the highly conserved GRFTLRD motif plays a crucial role in mediating eRF1 binding (Kong et al 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Recent data suggest that GTP hydrolysis by eRF3 couples stop codon recognition by eRF1 with peptidyl-tRNA hydrolysis by the peptidyl transferase center (Salas-Marco and Bedwell 2004; Alkalaeva et al 2006). eRF1 and eRF3 form a stable complex through interaction of their C-terminal domains (Ito et al 1998;Ebihara and Nakamura 1999;Merkulova et al 1999). Studies of the interaction of guanine nucleotides with eRF3 alone and with the eRF3deRF1 complex show that GTP and eRF1 bind to eRF3 with strong positive cooperativity (Hauryliuk et al 2006;Pisareva et al 2006) and that the stimulatory effect of eRF1 on binding of eRF3 to GTP strongly depends on the presence of Mg 2+ .…”
Section: Introductionmentioning
confidence: 99%
“…It was also shown that the products of SUP45 (eRF1) and SUP35 (eRF3) interact in vitro (Stansfield et al 1995b;Zhouravleva et al, 1995). This interaction is mediated by the C-terminal part of eRF1, although there are some discrepancies about the precise localization of the region of eRF1 that interacts with eRF3 Ebihara and Nakamura, 1999;Eurwilaichitr et al, 1999;Merkulova et al, 1999). The deletion of the C-terminal 19 amino acids abolishes the interaction with eRF3 and causes an enhancement of nonsense suppression.…”
Section: Eukaryotic Release Factor 3 (Erf3)mentioning
confidence: 99%